Human-Centered Agriculture Ergonomics and Human Factors Applied - Nag, P. K.; Gite, L. P.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book explores the interplay of farm mechanization, human factors and climatic and other environmental uncertainty in agriculture, using an ergonomics based approach to discuss solutions to the traditionally acknowledged vulnerability of the sector. It converges contemporary research documentation, case studies and international standards on agricultural ergonomics, engineering anthropometry, human factors, basic occupational health services, safety management, human performance and system sustainability to provide a handy reference to students and professionals working to optimize agricultural output while balancing the rational utilization of labour in agricultural practices and human well-being. .
Part 1: Agriculture growth and development -- Ch 1- World Agriculture- an introduction -- Ch 2. Manpower utilization- Working methods and practices -- Part 2: Fundamentals of Ergonomics & Human Factors -- Ch 3- Fundamental of ergonomics and human factors -- Ch 4- Energy cost of human labour -- Ch 5- Work planning and schedules -- Ch 6. Engineering anthropometry -- Part 3: Farming methods and practices -- Ch 7- Mechanization: Nature of development -- Ch 8- Small tools and devices -- Ch 9- Manually operated machines -- Ch 10- Heavy machinery -- Part 4: Health and Safety -- Ch 11- Accidents and injuries -- Ch 12- Health hazards -- Ch 13- Pesticide and chemical toxicity -- Ch 14- Basic occupational health services -- Appendices.
Keywords: Engineering design; Personnel management; Agriculture; Environmental policy; Sociology; Employee health promotion; Engineering Design; Human Resource Management; Agriculture; Environmental Policy; Sociology, general; Employee Health and Wellbeing